The Prospects for Coal-to-Liquid Conversion: A General Equilibrium Analysis - Chen, Y. H. Henry (2012)
We investigate the economics of coal-to-liquid (CTL) conversion, a polygeneration technology that produces liquid fuels, chemicals, and electricity by coal gasification and Fischer-Tropsch process. CTL is more expensive than extant technologies when producing the same bundle of output. In addition, the significant carbon footprint of CTL may raise environmental concerns. However, as petroleum prices rise, this technology becomes more attractive especially in coal-abundant countries such as the U.S. and China. Furthermore, including a carbon capture and storage (CCS) option could greatly reduce its CO2 emissions at an added cost. To assess the prospects for CTL, we incorporate the engineering data for CTL from the U.S. Department of Energy (DOE) into the MIT Emissions Prediction and Policy Analysis (EPPA) model, a computable general equilibrium model of the global economy. Based on DOE's plant design that focuses mainly on liquid fuels production, we find that without climate policy, CTL has the potential to account for up to a third of the global liquid fuels supply by 2050 and at that level would supply about 4.6% of global electricity demand. A tight global climate policy, on the other hand, severely limits the potential role of the CTL even with the CCS option, especially if low-carbon biofuels are available. Under such a policy, world demand for petroleum products is greatly reduced, depletion of conventional petroleum is slowed, and so the price increase in crude oil is less, making CTL much less competitive.